2019
DOI: 10.1021/acs.langmuir.9b03469
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Effects of Acid, Alkali, and Salt Solutions on Fluorinated Superhydrophobic Surfaces

Abstract: Extensive studies have been carried out to investigate the stability of superhydrophobic surfaces under acid, alkali, and salt solutions. It is noted that previous literature studies just demonstrated a variety of experimental phenomena. However, very few works have focused on the protection mechanism or failure mechanism of fluorinated superhydrophobic surfaces from the perspective of chemical aspects. Herein, this paper aims to investigate the effects of acid, alkali, and salt solutions on the stability of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…This phenomenon implied that the strong alkaline solution had dramatically damaged the flat copper surface to generate rough micro/nano-structures, causing a huge change in surface wettability. Based on Wenzel theory, surface roughness has the amplifying effect on surface wettability, indicating that the increase of surface roughness results in smaller WCA on intrinsic hydrophilic surface or larger WCA on intrinsic hydrophobic surface [30,31].…”
Section: Surface Wettabilitymentioning
confidence: 99%
“…This phenomenon implied that the strong alkaline solution had dramatically damaged the flat copper surface to generate rough micro/nano-structures, causing a huge change in surface wettability. Based on Wenzel theory, surface roughness has the amplifying effect on surface wettability, indicating that the increase of surface roughness results in smaller WCA on intrinsic hydrophilic surface or larger WCA on intrinsic hydrophobic surface [30,31].…”
Section: Surface Wettabilitymentioning
confidence: 99%
“…Noticeably, NiTi-I had the lowest impedance modulus |Z| at the low frequency of 0.01 Hz, while Ni-Ti-III possessed the biggest impedance modulus |Z|. Previous literature had verified that the larger value of impedance modulus |Z| at the low frequency in Bode diagrams implies the better corrosion resistance [42,43] . Hence, both the Nyquist plots and Bode diagrams confirmed the excellent corrosion resistance of NiTi-III.…”
Section: Eis Testmentioning
confidence: 91%
“…As far as NiTi-II and NiTi-III, the better fitting results were obtained via the equivalent circuit displayed in Fig. 10b, where the electrolytic resistance is described by R s , the resistance between the passive film or the PDMS coating and corrosion solution is represented by R f , CPE f means the constant phase element and the corresponding value reflects the number of corrosion ions in contact with the film or coating [43] . CPE dl and R ct components represent the impedance of interface reaction between the NiTi substrate and the surface coating.…”
Section: Eis Testmentioning
confidence: 99%
“…These strategies may provide a significant improvement in the short term, but the performance of antiscaling rapidly declines with the loss of metal ions and scale inhibitors. Other researchers have shown that superhydrophobic coatings with low surface energy substances (such as F and Si) or with special structures constructed on the surface of the coating can effectively reduce fouling adhesion. Although this technology of a superhydrophobic coating has achieved excellent scale inhibition effects in the short term, it cannot overcome the drawback of a short lifetime at present.…”
Section: Introductionmentioning
confidence: 99%